PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) PADA KETERAMPILAN BERBICARA SISWA - Putu Putra Adnyana; Runimeirati Runimeirati (Yayasan Education and Social Center, 2021)
The application of NHT (Number Head Together) learning on speaking skills through discussion activities for class XI students at SMK Kristen Palopo. This type of devotion is experimental. Sampling in this service is purposive sampling. The technique used to collect data in this service is the initial test technique and the final test. The collected data was then analyzed using descriptive statistical techniques and inferential statistics. Based on the results of descriptive statistical analysis, it showed that there was an increase in the results of the pretest and posttest, namely speaking ability before the application of the NHT learning model (Number Head Together) obtained an average score of 61.00 with a standard deviation of 5.51 and speaking ability after application (Number Head Together). NHT was categorized as high with an average score of 80.16 with a standard deviation of 3.92. This is evidenced by the scores of students who reach 75 and above are categorized as complete and scores <75 and below are incomplete. The results showed that the application of the NHT (Number Head Together) learning model was able to be applied to speaking skills through discussion activities for Class XI students at SMK Kristen Palopo